Tunable Q-switched erbium-doped fiber laser using nickel oxide saturable absorber - Rizman, Zairi Ismael; Arof, Hamzah; Latiff, Anas Abdul; Apsari, Retna; Harun, Sulaiman Wadi (Old City Publishing, 2018)
We fabricated a Nickel oxide (NiO) polymer composite saturable absorber, and used it to passively generated Q-switch Erbium-doped fiber laser (EDFL). It was tunable from 1535 to 1565 nm. At operating wavelength of 1535 nm, the repetition rate of the self-starting Q-switching pulses could be increased from 17.9 kHz to 28.2 kHz while the pulse width reduced from 16.1 to 9.1 μs with increasing pump power from 14.9 to 37.7 mW. The highest slope efficiency of 22.11% was obtained at operating wavelength of 1540 nm. The output pulse energy increased from 139 nJ to 419 nJ as the pump power varied from 4.9 to 37.7 mW at the operating wavelength of 1565 nm. This saturable absorber forms a simple and cost-effective light source for environmental sensing, metrology and biomedical diagnostics.